TNFRSF13B Diversification Fueled by B Cell Responses to Environmental Challenges—A Hypothesis - Cascalho, Marilia; Platt, Jeffrey L. (Frontiers in Immunology, 2021)
B cell differentiation and memory are controlled by the transmembrane activator and CAML interactor (TACI), a receptor encoded by TNFRSF13B. TNFRSF13B mutations are frequently found in common variable immunodeficiency (CVID) and in IgA -deficiency; yet, 98% of those with mutant TNFRSF13B are healthy. Indeed, TNFRSF13B is among the 5% most polymorphic genes in man. Other mammals evidence polymorphism at comparable loci. We hypothesize that TNFRSF13B diversity might promote rather than detract from well-being by controlling key elements of innate immunity. We shall discuss how extraordinary diversity of TNFRSF13B could have evolved and persisted across diverse species of mammals by controlling innate and adaptive B cell responses in apparently paradoxical ways.